Pembangunan Website Informasi Kepegawaian Pada UPTD Teknologi Komunikasi Dan Informasi Pendidikan - Highness Mailani Putri; Indra Pradista; Ridha Anisa Soldzu Parnga; Wawan Joko Pranoto (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Information and Communication Technology (ICT) is a crucial element in modern life, encompassing the management, manipulation, and transfer of information across media platforms. UPTD Teknologi Komunikasi dan Informasi Pendidikan is a Structurally Integrated Service Unit under the East Kalimantan Provincial Education Office. UPTD plays a strategic role in providing technology-related services in the field of education. However, UPTD faces challenges in the inefficient and slow management of employee data, with 28 employees whose personnel data remains unoptimized. To enhance efficiency, the author plans to develop a web-based personnel information system. The problem statement includes inadequate system support, resulting in slow employee search and report generation processes. The objective of this system is to design an efficient, precise, and accurate personnel data management system, aiming to improve work productivity within UPTD Teknologi Komunikasi dan Informasi Pendidikan. The outcome of this initiative is the design of a website serving as an information portal for UPTD profile, developed using the Content Management System (CMS) WordPress.